Updated Evaluation of Robotic- and Video-Assisted Thoracoscopic Lobectomy or Segmentectomy for Lung Cancer: A Systematic Review and Meta-Analysis - Zhang, Jianyong; Feng, Qingbo; Huang, Yanruo; Ouyang, Lanwei; Luo, Fengming (Frontiers in Oncology, 2022)
Background: Robot-assisted thoracic surgery (RATS) and video-assisted thoracic surgery (VATS) are the two principal minimally invasive surgical approaches for patients with lung cancer. This study aimed to compare the long-term and short-term outcomes of RATS and VATS for lung cancer. Methods: A comprehensive search for studies that compared RATS versus VATS for lung cancer published until November 31, 2021, was conducted. Data on perioperative outcomes and oncologic outcomes were subjected to meta-analysis. PubMed, Web of Science and EMBASE were searched based on a defined search strategy to identify eligible studies before November 2021. Results: 26 studies comparing 45733 patients (14271 and 31462 underwent RATS and VATS) were included. The present meta-analysis showed that there were no significant differences in operative time, any complications, tumor size, chest drain duration, R0 resection rate, lymph station, 5 years overall survival and recurrence rate. However, compared with the VATS group, the less blood loss, a lower conversion rate to open, a shorter length of stay hospital, more lymph node dissection and a better 5 years disease-free survival were captured in RATS. Conclusions: RATS is a safe and feasible alternative to VATS and provide a better 5 years disease-free survival for patients with lung cancer.